High‐dose posaconazole for azole‐resistant aspergillosis and other difficult‐to‐treat mould infections. Issue 2 (15th December 2019) - Schauwvlieghe, Alexander F. A. D.; Buil, Jochem B.; Verweij, Paul E.; Hoek, Rogier A. S.; Cornelissen, Jan J.; Blijlevens, Nicole M .A.; Henriet, Stefanie S. V.; Rijnders, Bart J. A.; Brüggemann, Roger J. M.
Summary: Background: Oral follow‐up therapy is problematic in moulds with reduced azole‐susceptibility, such as azole‐resistant Aspergillus fumigatus infection. Currently, only intravenous liposomal amphotericin B (L‐AmB) is advocated by guidelines for the treatment of azole‐resistant aspergillosis infections. Preclinical research indicates that high‐dose posaconazole (HD‐POS) might be a feasible option provided that high drug exposure (ie POS serum through levels >3 mg/L) can be achieved and is safe. Objectives: To describe our experience with the use of oral HD‐POS as treatment strategies for patients infected with pathogens with a POS MIC close to the clinical breakpoint. Patients/Methods: We review evidence supporting the use of HD‐POS and describe our experience on safety and efficacy in 16 patients. In addition, we describe the adverse events (AE) observed in 25 patients with POS concentrations at the higher end of the population distribution during treatment with the licensed dose. Results: Sixteen patients were treated intentionally with HD‐POS for voriconazole‐resistant invasive aspergillosis (7/16), mucormycosis (4/16), salvage therapy for IA (4/16) and IA at a sanctuary site (spondylodiscitis) in 1. Grade 3‐4 AEs were observed in 6, and all of them were considered at least possibly related. Grade 3‐4 AEs were observed in 5 of the 25 patients with spontaneous high POS serum through levels considered at least possibly related using Naranjo scale. Conclusions: High‐dose posaconazole is a treatment option if strict monitoring for both exposure and for AE is possible.